2021
DOI: 10.1177/09645284211056663
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves metabolic and ovarian function in a rat model of polycystic ovary syndrome by decreasing white adipose tissue, increasing brown adipose tissue, and modulating the gut microbiota

Abstract: Background: Polycystic ovary syndrome (PCOS) affects 8%–15% of reproductive-age women and is associated with reproductive disorders, abdominal obesity, hyperinsulinemia, insulin resistance, type 2 diabetes, and cardiovascular diseases. Acupuncture, as a traditional physical therapy method, could affect various metabolic disorders such as obesity, hyperplasia, gout, and cardiovascular and cerebrovascular diseases in clinical practice. Moreover, electroacupuncture (EA) has been shown to decrease body weight in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Past studies have suggested that EA could modulate intestinal microecology and protect the intestinal barrier [ 41 43 ]. Zhang et al showed that EA regulated the metabolic disorders and improved reproductive function in this PCOS-like rat model by adjusting intestinal microbiota [ 24 ]. Similarly, we found that EA has positive effects on both restoration of the percentage of normal follicles and improvement of intestinal microbiota disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have suggested that EA could modulate intestinal microecology and protect the intestinal barrier [ 41 43 ]. Zhang et al showed that EA regulated the metabolic disorders and improved reproductive function in this PCOS-like rat model by adjusting intestinal microbiota [ 24 ]. Similarly, we found that EA has positive effects on both restoration of the percentage of normal follicles and improvement of intestinal microbiota disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Some underlying mechanisms of EA for POF have been confirmed that EA could inhibit follicular loss, activate serum anti-Müllerian hormone (AMH), and enhance activation of antioxidative and antiapoptotic [21][22][23]. In addition, EA can improve reproductive function by reshaping and adjusting the abundance of the intestinal microbiota [24]. But whether EA can regulate the intestinal microbiota of POF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the gut microbiota is known to be causal in the development of obesity/insulin resistance ( 111 ). A recent study showed that EA intervention decreased body weight, probably through regulating gut microbiota in PCOS rats ( 112 ). This study also demonstrated that EA can normalize visceral and subcutaneous fat content, brown adipose tissue weight, and glucose tolerance in the PCOS model.…”
Section: Potential Mechanisms Of Acupuncture Affecting Pcos-related S...mentioning
confidence: 99%
“…Acupuncture and Chinese herb medicines (CHMs) have signi cant e cacy in improving menstruation [7], ovulation [6][8], pregnancy [7][8] [9] [21], body weight [9], insulin resistance [9][10] [11] [24], sex hormones [7][23] [24] regulation of intestinal ora [9] [20], mood [12], and sleep in patients with PCOS. Therefore, Chinese medicine treatments have a wide range of positive signi cance for patients with polycystic ovary syndrome.…”
Section: Introductionmentioning
confidence: 99%